HIV pre‐exposure prophylaxis for people who inject drugs: a review of current results and an agenda for future research. Issue 2 (27th March 2014) - Escudero, Daniel J; Lurie, Mark N; Kerr, Thomas; Howe, Chanelle J; Marshall, Brandon DL
Abstract : Introduction: Studies examining the use of pre‐exposure prophylaxis (PrEP) to prevent HIV transmission among people who inject drugs (PWIDs) have not been adequately summarized. Recently, the Bangkok Tenofovir Study has shown that PrEP may be effective at reducing new HIV infections among this high‐risk group. This randomized controlled trial was the first study to specifically examine the efficacy of PrEP among PWIDs. In this review, we present the current state of evidence regarding the use of PrEP to prevent HIV infection in PWID populations, and set an agenda for future research to inform the most effective implementation of PrEP in the context of existing evidence‐based HIV prevention strategies. Discussion: Despite positive trial results confirming that PrEP may prevent HIV transmission among PWIDs, there remain many questions regarding the interpretation of these results, as well as obstacles to the implementation of PrEP regimens within highly diverse drug‐using communities. Aside from the Bangkok Tenofovir Study, we identified only one other published study that has collected empirical data to inform the use of PrEP among PWIDs. The large gap in research regarding the use and implementation of PrEP for PWIDs signals the need for further research and attention. Conclusions: We recommend that future research efforts focus on elucidating the generalizability of the Bangkok Tenofovir Study results in other injection drug–using populations, examining the willingness of PWIDs to use PrEP in diverse contexts, identifying barriers to adherence to PrEP regimens and determining the most effective ways to implement PrEP programmes within the context of existing evidence‐based prevention strategies, including opioid substitution therapy and needle and syringe distribution programmes.